Consider a thin and infinitely stretchable rubber rope held taut along the -axis with a starting point marked at and a target point marked at At the instant the rope starts to stretch uniformly and smoothly in such a way that the starting point remains stationary and the target point moves away from the starting point with constant speed A small ant leaves the starting point at the same time the rubber rope starts to stretch and walks steadily and smoothly along the rope towards the target point at a constant speed relative to the point on the rope where the ant is at each moment. Then the ant will hit the target point at time
where and are all integers. Find
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let the ant's position as a function of time be x . At first it seems that the ant's movement is simply d t d x = α , but this doesn't factor in the stretching of the rope. As the rope extends the section of rope behind the ant will extend as well, pushing the ant forward an additional amount.
As end of the rope stretches forward at a speed of v , the ant will move forward at some fraction of v equal to the fraction of the rope the ant has covered, since the stretching is distributed equally across the entire rope. At any point in time, the rope has a length of c + v t , and so the ant will have gone a fraction of c + v t x . Therefore the speed of the ant due to the stretching is c + v t v x and so the total speed is d t d x = c + v t v x + α .
This results in a linear first-order differential equation:
d t d x − c + v t v x = α
To solve this, we first find the integrating factor, μ ( t ) = e ∫ p ( t ) d t
μ ( t ) = e ∫ − c + v t v d t = e − ln ( c + v t ) + C 0 = e ln ( c + v t ) e C 0 = c + v t K Where the constant K = e C 0
Then we multiply the integrating factor through the differential equation, resulting in a product rule form on the left hand side:
c + v t K d t d x − ( c + v t ) 2 K v x c + v t K ⋅ d t d ( x ) − d t d ( c + v t K ) ⋅ x d t d ( c + v t K ⋅ x ) c + v t K x = c + v t K α = c + v t K α = c + v t K α = ∫ c + v t K α d t = v K α ln ( c + v t ) + C
When t = 0 , x = 0 , so
v K α ln ( c ) + C C ∴ c + v t K x c + v t K x x = 0 = − v K α ln ( c ) = v K α ln ( c + v t ) − v K α ln ( c ) = v K α ln ( c c + v t ) = v α ( c + v t ) ln ( 1 + c v t )
Now we need to find when the position of the ant equals the position of the end of the rope, so:
v α ( c + v t ) ln ( 1 + c v t ) ln ( 1 + c v t ) 1 + c v t c v t t = c + v t = α v = e v / α = e v / α − 1 = v c ( e v / α − 1 )
Therefore A = 1 , B = 1 , C = − 1 , so the answer is ( 1 + 1 ) − 1 = 0 . 5